Pengelolaan Kurikulum Pembelajaran di MA PPMII Assalam - Ayu Novitasari (Jurnal Ekonomi Manajemen Perbankan, 2025)
Student management encompasses planning, selection, development, and supervision throughout the educational process at school. Teachers play a vital role in adapting the curriculum and instructional strategies to meet the individual learning needs of each student. To enhance motivation and active participation, engaging teaching methods such as Problem-Based Learning, group discussions, and contextual approaches relevant to students' daily lives are utilized. Learning obstacles are identified through mentoring, root cause analysis, and open communication with students and parents. Academic and behavioral progress is monitored through assessments of knowledge and attitude, such as the use of daily journals. Communication between school and parents is established through parent-teacher meetings, WhatsApp groups, and home visits to create synergy in supporting the students' learning process. Effective planning strategies can significantly contribute to the achievement of established learning goals. Curriculum management in educational institutions is a crucial factor in ensuring the effectiveness of learning. MA PPMI Assalaam, as an Islamic educational institution, implements an integrative approach by combining national curricula from the Ministry of Religious Affairs (Kemenag) and the Ministry of Education and Culture (Kemendikbud) with the distinctive Islamic content of pesantren. This study used a descriptive qualitative method through observation, interviews, and document analysis. The results show that MA PPMI Assalaam has developed flagship programs such as Dirosah Islamiyah and Riset Preneur. Curriculum evaluation is conducted regularly to maintain its relevance and effectiveness in supporting students’ academic and character development. However, challenges remain, such as limited resources and the dynamic nature of national education policies. Therefore, innovative and adaptive curriculum management strategies are essential to continuously improve the quality of education at MA PPMI Assalaam in line with the demands of the times.